The Otolaryngology Match 2019: Why Was This Year Different from Every Other Year?. (February 2020) - Eisenman, David J.; Guardiani, Elizabeth
After 2 years with record high numbers of unfilled spots in the otolaryngology National Residency Matching Program–sponsored match, the current match cycle had no open positions available in the Supplemental Offer and Acceptance Program. This article analyzes the historical and present data to try to understand what happened so that we can better avoid repeating the problems of the past.